A statistical determination of the contribution of viscoelasticity of aqueous carbohydrate polymer networks to drug release. (15th February 2019) - Jones, David S.; Yu, T.; Andrews, Gavin P.
Graphical abstract: Highlights: Interactive networks composed of hydroxyethylcellulose (HEC) and poly(vinylpyrrolidone) (PVP) were produced. The viscoelastic/mechanical properties of, and drug release from the interactive networks were characterised. Rheological synergy was observed between HEC and PVP, leading to the production of networks with a range of viscoelastic properties. The mechanism of drug release from the networks ranged from swelling/erosion to diffusion controlled and was only statistically dependent on the concentration of HEC. A limited correlation between network viscosity and drug release was observed. Abstract: In this study the relationship between the viscoelasticity/mechanical properties of metronidazole-containing aqueous polymer networks composed of HEC and PVP and drug release was statistically modelled. The networks were characterised using oscillatory analysis and drug release was performed using dissolution analysis (pH 7.4). Statistical modelling of the rheological properties and their relationship with drug release was performed using Analysis of Variance, Multivariate Analysis of Variance and stepwise regression. Modelling of drug release was performed using both the Korsmeyer-Peppas and Peppas-Sahlin models to understand the mechanism of drug release and the contributions of network swelling/erosion and diffusion on drug release. HEC and PVP were shown to significantly enhance the rheological properties of the networks. Furthermore, rheological synergy was observed whenever PVP was added to HEC and was due to non-covalent bond formation between these polymers. The magnitude of this synergy increased as functions of increasing concentrations of each polymer. Drug release was dependent on the concentration of HEC and independent of the presence of PVP. The release of metronidazole from networks composed of HEC 3% w/w and PVP (1–5% w/w) was controlled by network swelling/erosion whereas for the networks containing PVP and 5% and 10% w/w HEC, the dominant mechanism of drug release was diffusion. Limited correlation was observed between network rheological properties and drug release. It is suggested that this is due to dissociation of the HEC-PVP interactions and dissolution of PVP during drug release, resulting in a network structure whose properties are dominated by those of HEC. This is the first study that has statistically examined the role of binary polymer network viscoelasticity on drug release. Based on the findings of this study, caution should be shown when formulating aqueous networks with enhanced rheological properties as these effects may not necessarily contribute to other primary determinants of device performance, notably drug release.